2017
DOI: 10.1073/pnas.1712321115
|View full text |Cite
|
Sign up to set email alerts
|

Multiple origins of interdependent endosymbiotic complexes in a genus of cicadas

Abstract: Bacterial endosymbionts that provide nutrients to hosts often have genomes that are extremely stable in structure and gene content. In contrast, the genome of the endosymbiont has fractured into multiple distinct lineages in some species of the cicada genus To better understand the frequency, timing, and outcomes of lineage splitting throughout this cicada genus, we sampled cicadas over three field seasons in Chile and performed genomics and microscopy on representative samples. We found that a single ancestra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
163
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(173 citation statements)
references
References 50 publications
(72 reference statements)
7
163
3
Order By: Relevance
“…Indeed, ancestral Coxiella ‐LE may have evolved overly reduced (degraded) genomes and become maladapted, opening the road to replacement by a new symbiont. This degeneration–replacement model has been proposed for other arthropods such as cicadas (Campbell et al, ; Łukasik et al, ; Matsuura et al, ), but replacements are expected to be transient making them difficult to observe (McCutcheon et al, ). In Amblyomma , the observations of three species with co‐infections by ancestral Coxiella ‐LE and recently acquired Francisella ‐LE may correspond to this transient state before extinction of Coxiella ‐LE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, ancestral Coxiella ‐LE may have evolved overly reduced (degraded) genomes and become maladapted, opening the road to replacement by a new symbiont. This degeneration–replacement model has been proposed for other arthropods such as cicadas (Campbell et al, ; Łukasik et al, ; Matsuura et al, ), but replacements are expected to be transient making them difficult to observe (McCutcheon et al, ). In Amblyomma , the observations of three species with co‐infections by ancestral Coxiella ‐LE and recently acquired Francisella ‐LE may correspond to this transient state before extinction of Coxiella ‐LE.…”
Section: Discussionmentioning
confidence: 99%
“…This degeneration-replacement model has been proposed for other arthropods such as cicadas (Campbell et al, 2015;Łukasik et al, 2018;Matsuura et al, 2018) That ecological specialization to strict haematophagy is driven by nutritional symbiotic interactions is beyond doubt for ticks.…”
Section: Fl Ofmentioning
confidence: 91%
“…Although RNase Y is typically thought to initiate mRNA decay, it is also implicated in multiple RNA processing tasks (59). No such putative enzyme can be found in the D. semicinta Hodgkinia genome, although a gene for the endoribonuclease YbeY is present in Hodgkinia genomes from other cicada species (14). After 3' tRNA trailers are trimmed, a terminal CCA is added by a CCA-adding enzyme (30).…”
Section: ' Trna Processing Can Be Explained From the Genomes Of Sulcmentioning
confidence: 99%
“…Sulcia muelleri" (Bacteroidetes; hereafter Hodgkinia and Sulcia) have two of the smallest bacterial genomes published. Sulcia and Hodgkinia are obligate nutritional endosymbionts of many cicadas (13,14). In the cicada Diceroprocta semicincta, the Hodgkinia genome is 143 kilobases (kb) and the Sulcia genome is 277 kb.…”
Section: Introductionmentioning
confidence: 99%
“…In many of the cicada species characterized to date (but see (13)), these nutritional services are provided by two transovarially transmitted bacterial endosymbionts, Candidatus Sulcia muelleri (hereafter referred to as Sulcia) and Candidatus Hodgkinia cicadicola (hereafter Hodgkinia) (14)(15)(16). We have previously shown that in two cicada genera, Tettigades and Magicicada, Hodgkinia has undergone an unusual form of lineage splitting (17)(18)(19)(20). In some of these cicada species, a single Hodgkinia lineage has split into two or more derived lineages, each containing only a subset of the genes present in the single ancestral lineage.…”
Section: Introductionmentioning
confidence: 99%